2017
DOI: 10.3892/mmr.2017.6262
|View full text |Cite
|
Sign up to set email alerts
|

LMTK3 knockdown retards cell growth and invasion and promotes apoptosis in thyroid cancer

Abstract: Lemur tyrosine kinase-3 (LMTK3) is a member of the serine/threonine tyrosine kinase family, which is thought to be involved in tumor progression and prognosis. The purpose of the present study was to determine the diagnostic significance and therapeutic targets in thyroid cancer. ELISA assay was used to detect the protein expression of serum LMTK3. Immunohistochemistry and reverse transcription-quantitative polymerase chain reaction were employed to measure the expression of LMTK3. Flow cytometry was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…LMTK3 has been reported to be involved in several cancer types (5,7,11,(14)(15)(16). However, the lack of crystal structure has impeded an understanding of the role of this protein and its interactions with other molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMTK3 has been reported to be involved in several cancer types (5,7,11,(14)(15)(16). However, the lack of crystal structure has impeded an understanding of the role of this protein and its interactions with other molecules.…”
Section: Discussionmentioning
confidence: 99%
“…S3C). We also pinpointed Ser 15 and Ser 82 as the main HSP27 residues phosphorylated by LMTK3 in vitro, using site-directed mutagenesis ( fig. S3D), while both sites were in accordance with the identified LMTK3 phospho-motif.…”
Section: Determination Of the Lmtk3 Consensus Phosphorylation Motif Amentioning
confidence: 99%
“…Further studies clarified that LMTK3 may regulate these biological functions by the ERK/MAPK signaling pathway. Emerging evidence showed that LMTK3 played a pivotal role in the tumorigenesis and progression of most cancers [2][3][4]. In 2011, Giamas et al [8] identified LMTK3 as a therapeutic target in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…indirectly participate in a variety of cell signaling pathway transductions, such as estrogen receptor pathway, Wnt signaling pathway and forkhead box O3 pathway, among others. Previous research found that LMTK3 is highly expressed in many malignant tumors; its high expression is significantly correlated with the oncogenesis, progression and prognosis of various tumors [2][3][4]. Zhang et al [5] found that LMTK3 is a novel biomarker for primary non-small cell lung cancer, and high expression of LMTK3 predicts unfavorable clinical prognosis.…”
Section: It Can Catalyze Protein Phosphorylation and Directly Ormentioning
confidence: 99%
“…Lemur tyrosine kinase 3 (LMTK3) is a serine-threonine-tyrosine protein kinase involved in various cancers. Aberrant expression of the gene and polymorphisms within the gene serve as suitable biomarkers in cancer progression (350, 351). LMTK3 is expressed in both ER+ and ER-negative BCs and a kinome screen identified it as an ERα regulator (352).…”
Section: Other Transcription Factorsmentioning
confidence: 99%